Truth or Myth: Is Breast Implant Illness Really an Illness? - Rami Hanna, MD; Udi Maor, MD; Meir Retchkiman, MD; Basel Abu-Ganem, MD; Julie Vaynshtein, MD; Eldad Silberstein, MD (Plastic and Reconstructive Surgery, Global Open)
Background:. Breast implant illness (BII) represents symptoms linked to silicone gel–filled breast implants. Research on BII remains limited, yielding contradictory conclusions. This study compared symptoms among healthy women with breast implants to those without breast implants. Methods:. A single-blind questionnaire-based survey of asymptomatic female patients attending cancer screening was conducted at the Breast Health Center in Soroka Medical Center and at a breast surgeon’s community clinic in Beer Sheva, Israel. The study included women with breast implants (implanted group) and those without implants or any other breast procedures (naive group). The questionnaire collected social, medical, and symptom data, stratified using the Index of Symptoms’ Severity (ISS) scale. Results:. Out of 181 women, 13 were excluded. The implanted group (n = 34) was compared with women without prior breast surgery, including implants (n = 134). Significant differences emerged in dry skin and sleeping problems, with higher rates in the naive group. However, overall symptom severity, measured by the ISS, showed no significant difference. Regression analysis indicated age and rheumatoid history correlated with the ISS, whereas breast implant augmentation was not a significant predictor. Conclusions:. This study explored BII prevalence by comparing symptoms in women with breast implants to those without prior breast surgical interventions. Overall, symptom severity demonstrated no significant differences. Age and preexisting rheumatoid conditions may influence symptoms more than breast augmentation. The study’s cross-sectional design, small sample size, and self-reported data could limit its findings. Further research is needed to understand BII’s impact on well-being and safety.